Catalan Numbers, Riccati Equations and Convergence - Feng, Yicheng; Fouque, Jean-Pierre; Ichiba, Tomoyuki (European Journal of Applied Sciences, 2024)
We analyze both finite and infinite systems of Riccati equations derived from stochastic differential games on infinite networks. We discuss a connection to the Catalan numbers and the convergence of the Catalan functions by Fourier transforms.